NEPHRO-PROTECTIVE ACTIVITY OF ISOLATED METHANOL FRACTIONS PHYTO-COMPOUND FROM BARK OF TERMINALIA ARJUNA - Mandal, Shreya; Patra, Arpita; Pradhan, Shrabani; Roy, Suchismita; Samanta, Animesh; Das, Koushik; Chattopadhyay, Atiskumar; Nandi, Dilip Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The aim of this study was to evaluate the antioxidant property of the isolated phytocompounds from TA (Terminalia arjuna) bark and in vivo study for nephro-protective and oxidative stress reducing activity in experimentally induced albino male rats. Methods: Fractions from methanol crude TA extract were collected by column chromatography and F27, F28, F29 fractions were selected on the basis of antioxidant property by 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay. The in vivo study performed by 30 albino male rats which were randomly divided into five groups: Group I (control)were taken normal food and water, Groups II (uremic) were injected acetaminophen intraperitoneally at the dose of 500 mg/kg/d for 10 d, Group III, IV and V(extract treatment) acetaminophen intraperitoneally at the dose of 500 mg/kg/d for 10 d with co-administered orally of methanol fraction F27, F28, F29 at the dose of 100 mg/kg/d for 15 d respectively. Results: After scarification of rats, the uremic marker plasma urea (80%), creatinine (85%) were elevated and antioxidant enzyme marker such as plasma SOD and catalase level were significantly increased (p<0.05)in Group IV compared to Group II. The total phenolic content of the F28 methanolic fraction was (815.48Â±8.11) mg gallic acid equivalent/g of extract. For isolation of available compound by 1H NMR study in F28 methanol fraction of TA bark was arjunoside IV which contained olefinic proton (a pair of carbon atom linked with double bond). Conclusion: Among the three methanolic fraction of TA bark, F28 was shown best antioxidative, nephron-protective and oxidative stress reducing property.Â 